Sperm selection by rheotaxis improves sperm quality and early embryo development. Issue 3 (March 2021) - Romero-Aguirregomezcorta, Jon; Laguna-Barraza, Ricardo; Fernández-González, Raúl; Štiavnická, Miriama; Ward, Fabian; Cloherty, Jennifer; McAuliffe, Denis; Larsen, Peter B; Grabrucker, Andreas M; Gutiérrez-Adán, Alfonso; Newport, David; Fair, Seán
Abstract : The objective of this work was to elucidate whether a sperm selection method that combines rheotaxis and microfluidics can improve the selection of spermatozoa over density gradient and swim-up. For this purpose human sperm selected by rheotaxis were compared against density gradient, swim-up and a control group of non-selected spermatozoa in split frozen-thawed (FT) and fresh (F) semen samples. Sperm quality was assessed in terms of motility, morphology, DNA fragmentation index (DFI), viability, acrosome integrity and membrane fluidity. Using a mouse model, we compared fertilisation and embryo development rates after performing ICSI with spermatozoa, sorted using rheotaxis or swim-up. Selection by rheotaxis yielded a sperm population with reduced DFI than the control ( P  < 0.05), improved normal morphology ( P  < 0.001) and higher total motility (TM; P  < 0.001) than the other techniques studied in F and FT samples. Swim-up increased TM compared to density gradient and control in FT or F samples ( P  < 0.001), and yielded lower DFI than the control with F samples ( P  < 0.05). In FT samples, selection by rheotaxis yielded sperm with higher viability than control, density gradient and swim-up ( P  < 0.01) while acrosomal integrity and membrane fluidity were maintained. When mouse spermatozoa were selected for ICSI using rheotaxis compared to swim-up, there was an increase in fertilisation ( P  < 0.01), implantation ( P  < 0.001) and foetal development rates ( P  < 0.05). These results suggest that, in the absence of non-destructive DNA testing, the positive rheotaxis can be used to select a population of low DNA fragmentation spermatozoa with high motility, morphology and viability, leading to improved embryo developmental rates.